Variasi Lama Perendaman dan Konsentrasi Phenol Formaldehida terhadap Kualitas Papan Lamina dari Batang Kelapa Sawit - Syafrina Talenta Lumbangaol; Rudi Hartono; Tito Sucipto (Program studi Kehutanan USU, 2015)
One way to approve laminated board quality of palm oil trunk was soaked the laminated board with phenol formaldehyda (PF). The purpose of this study was to evaluate the influence soaking time variation and concentration PF than to determine the best treatment in this research. Laminated board was consisted 3 (three) layers with size 45 cm (length) x 7 cm (width) x 3 cm (thick). The variation of these research were soaking time (10 minutes, 2 hours, and 24 hours) and PF concentration (5.10.15. and 20% ). These study used random experimental factorial design and the results were compared with JAS 243:2003 standard. Results showed weight gain value, density, moisture content, water absorption 2 hours and 24 hours, thickness swelling on immersion 2 hours and 24 hours, thickness swelling on immersion 2 hours and 24 hours around, delamination test, modulus of rupture, and modulus of elasticity. Result showed that 3.82-15%, 0.39-0.47 g/cm3, 11.66-14.16%, 36.15-46.38%, and 78.87-98.65%, 2.5-11.58% and 5.13-17.58, 0%, 170.23-250.15 kg/cm2, and 17224-43767 kg/cm2. Moisture content and delamination values have fulfilled JAS 243:2003 standard. The other hand, MOE and MOR values were not fulfilled yet. The best treatment laminated board made from palm oil trunk was to immerse 10 minutes consentration 15%.